Authenticity: what consumers really want - Gilmore, James H.; Pine II, B. Joseph (Boston, Ma., 2007)
"Contrived. Disingenuous. Phony. Inauthentic. Do your customers use any of these words to describe what you sell—or how you sell it? If so, welcome to the club. Inundated by fakes and sophisticated counterfeits, people increasingly see the world in terms of real or fake. They would rather buy something real from someone genuine rather than something fake from some phony. When deciding to buy, consumers judge an offering's (and a company's) authenticity as much as—if not more than—price, quality, and availability. In Authenticity, James H. Gilmore and B. Joseph Pine II argue that to trounce rivals companies must grasp, manage, and excel at rendering authenticity. Through examples from a wide array of industries as well as government, nonprofit, education, and religious sectors, the authors show how to manage customers' perception of authenticity by: recognizing how businesses "fake it;" appealing to the five different genres of authenticity; charting how to be "true to self" and what you say you are; and crafting and implementing business strategies for rendering authenticity. The first to explore what authenticity really means for businesses and how companies can approach it both thoughtfully and thoroughly, this book is a must-read for any organization seeking to fulfill consumers' intensifying demand for the real deal."